Impact of overload factor on uplink SCMA system - Hongyang ZHANG; Changliang ZHENG; Yu LU; Huaping LIU (Dianxin kexue, 2018)
Sparse code multiple access (SCMA) is regarded as a promising multiple access technology for 5G because of its excellent performance.One of the major challenges that 5G networks are facing is the massive connectivity in terms of both data volume and the number of devices,thus SCMA must be capable of coping with transmission overload.Analyzing the performance of the uplink SCMA system in overloading scenarios was focused on.At first,the influence of the overloading factor on the detection and decoding complexities and error performances of the uplink SCMA system were analyzed.Then,by establishing the relationship between the overloading factor and the average sum-rate,the impact of the overloading factor on the transmission rate of the uplink SCMA system was analyzed.Extensive numerical results are provided to verify the accuracy and insights derivable from the analytical results.